2020
DOI: 10.1002/cb.1880
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mobile payment on consumer behavior

Abstract: With the advancement of technology and diversification of payment methods, mobile payment methods have gradually replaced traditional cash payments and become the mainstream payment mode. Although mobile payment is more convenient, is it faster than cash payment when their physical differences are controlled? Does it affect consumer behavior? We designed two studies to explore these questions. In Study 1, we required 192 participants to physically pay by cash or mobile phone and measured their willingness to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…Consumers’ willingness to pay (WTP) is often used to analyze their purchasing intentions [ 8 , 9 , 10 , 11 ]. WTP usually refers to the maximum amount of money that a consumer is willing to pay in exchange for a unit of goods or service.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers’ willingness to pay (WTP) is often used to analyze their purchasing intentions [ 8 , 9 , 10 , 11 ]. WTP usually refers to the maximum amount of money that a consumer is willing to pay in exchange for a unit of goods or service.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the method of payment and other factors, the transaction waiting time can be from a few seconds [68], if the payment is made by bank card or mobile payment, or a few minutes (in the case of cash payment) to several hours or even days (waiting for a bitcoin transaction to be confirmed (based on blockchain technology) at a certain time point lasted 3380 min) [69][70][71]. The acceleration of the transaction time has been facilitated by the implementation of NFC in payments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Payment methods such as credit cards psychologically decouple consumption from payment by delaying payment until the credit card bill is due (Prelec and Loewenstein, 1998;Soman and Gourville, 2001). With the recent increase in online shopping using smartphones, research has shown that mobile payment also lowers pain of payment and increases willingness to pay for products (Falk et al, 2016;Liu et al, 2020).…”
Section: The Moderating Effect Of Mental Budgetingmentioning
confidence: 99%